Practices Towards an Effective Response to Climate and Energy Challenges in The Al-Muthanna University Campus - Ahmed A. Rashid Kbah; Muna Alsallal; Hadel Saad Razoki Al-Mur'Ib; Ali Saad Al-Rubay (Universitas Diponegoro, 2023)
Regarding the UN reports, Climate change adaptation and mitigation stands for the most difficult challenge for the current and subsequent years in the world, in addition to the particular case of Iraqi cities, especially with the dry, hot climate and Power generation problems. Al-Muthanna University, during the last five years, focused on using the essential tools depending on NBS for saving energy (using daylight, rainwater, and natural materials) and also using innovative solutions (led light, sensors, solar panels, remote sensing) for reducing energy consumption in the Campus, Greenhouse gas emission the University reduce it by reducing the energy consumption itself, encouraging staff to use Liquid Gas Fuel Automotive, increase the green area, cycling. Therefore, the approximate use of energy-efficient applicants (particularly LED lamps and laptops) is around 75%. It is also good to mention that there is a total area of smart buildings of 82150 m2 across all campuses of Al-Muthanna University. In addition, the total Carbon footprint in 2021 equals 90.83 metric tons.